2007
DOI: 10.3201/eid1303.060242
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania donovaniand Cutaneous Leishmaniasis, Sri Lanka

Abstract: To investigate the relationship of cutaneous leishmaniasis isolates from Sri Lanka to known species, we performed DNA sequencing and microsatellite analyses. We identified Leishmania donovani as the agent of Sri Lanka cutaneous leishmaniasis and showed that these parasites are closely related to those causing visceral leishmaniasis in the Indian subcontinent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
91
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(97 citation statements)
references
References 15 publications
(28 reference statements)
6
91
0
Order By: Relevance
“…In 2003, the causative species was identified as Leishmania donovani zymodeme MON-37 (6). DNA sequencing and microsatellite analyses showed that these parasites are closely related to those causing visceral leishmaniasis in the Indian subcontinent (7). Mucocutaneous and visceral involvements were first reported in 2005 (8) and 2007 (9) respectively in Anuradhapura.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2003, the causative species was identified as Leishmania donovani zymodeme MON-37 (6). DNA sequencing and microsatellite analyses showed that these parasites are closely related to those causing visceral leishmaniasis in the Indian subcontinent (7). Mucocutaneous and visceral involvements were first reported in 2005 (8) and 2007 (9) respectively in Anuradhapura.…”
Section: Introductionmentioning
confidence: 99%
“…There were six cases of visceral Leishmaniasis (10,11). Until recent years, this has been a neglected disease locally and was thought to be a disease of military personnel (6,7). Recent literature (10,11,13,14) showed that this was a disease of locals, where farmers and children who engaged in outdoor activities were the mostly affected.…”
Section: Introductionmentioning
confidence: 99%
“…DNA sequencing and microsatellite analyses have shown that these parasites are closely related to those causing VL in the Indian subcontinent (L. donovani, MON-2). 6,7 The term "leishmaniasis" encompasses a spectrum of acute or chronic cutaneous and visceral diseases. Evidence has shown that resistance to Leishmania infection is mainly due to the cellular immune response of the host, which results in leishmaniacidal macrophage activation.…”
Section: Introductionmentioning
confidence: 99%
“…Multilocus enzyme electrophoresis characterized cutaneous L. donovani strains from Sri Lanka as zymodeme MON-37 (Karunaweera et al, 2003), which differs from India, where VL is predominantly caused by L. donovani zymodeme MON-2. DNA sequencing and microsatellite analyses demonstrated that Indian and Sri Lankan L. donovani strains are genetically similar, but highlighted the important biological differences between geographically close parasites (Siriwardana et al, 2007).…”
mentioning
confidence: 99%